Graphdiyene enables ultrafine Cu nanoparticles to selectively reduce CO2 to C2+ products - Chang, Yong-Bin; Zhang, Chao; Lu, Xiu-Li; Zhang, Wen; Lu, Tong-Bu (Nano research, 2022)
Reducing the size of heterogeneous nanocatalysts is generally conducive to improving their atomic utilization and activities in various catalytic reactions. However, this strategy has proven less effective for Cu-based electrocatalysts for the reduction of CO 2 to multicarbon (C 2+ ) products, owing to the overly strong binding of intermediates on small-sized (< 15 nm) Cu nanoparticles (NPs). Herein, by incorporating pyrenyl-graphdiyne (Pyr-GDY), we successfully endowed ultrafine (∼ 2 nm) Cu NPs with a significantly elevated selectivity for CO 2 -to-C 2+ conversion. The Pyr-GDY can not only help to relax the overly strong binding between adsorbed H* and CO* intermediates on Cu NPs by tailoring the d-band center of the catalyst, but also stabilize the ultrafine Cu NPs through the high affinity between alkyne moieties and Cu NPs. The resulting Pyr-GDY-Cu composite catalyst gave a Faradic efficiency (FE) for C 2+ products up to 74%, significantly higher than those of support-free Cu NPs (C 2+ FE, ~ 2%), carbon nanotube-supported Cu NPs (CNT-Cu, C 2+ FE, ~ 18%), graphene oxide-supported Cu NPs (GO-Cu, C 2+ FE, ~ 8%), and other reported ultrafine Cu NPs. Our results demonstrate the critical influence of graphdiyne on the selectivity of Cu-catalyzed CO 2 electroreduction, and showcase the prospect for ultrafine Cu NPs catalysts to convert CO 2 into value-added C 2+ products.